(untitled) (International Journal of Engineering and Computer Science, 2014)
the safety and comfort aspects of passenger car are significant sales argument and it become a topic of rising importance during development process of new car. Maintaining adequate visibility at all times through a vehicle windshield is important. Vehicle Defrost systems are required to defrost the windshield and side windows in considerable time after the blower has been switched on. The ability of windshield defrosting and demisting system to quickly and completely melt ice on the outer windshield surface and mist formed on the inner surface is therefore is important. The current study gives methodology for Computational techniques used in industries to evaluate actual performance of defrost/demist system of automobile at manufacturing stage. Some experimental and computational efforts are elaborated in this paper from previous studies so as to study current scenario in Windshield defroster system. This paper summarizes state of knowledge for improving evaluation efforts. The objective of this study is to enhance computational techniques to get improved outcome.